Peer Effects in the Workplace - Thomas Cornelissen; Christian Dustmann; Uta Schönberg (Center for Economic Studies and ifo Institute (CESifo), 2013)
Existing evidence on peer effects in a work environment stems from either laboratory experiments or from real-word studies referring to a specific firm or specific occupation. Yet, it is unclear to what extent these findings apply to the labor market in general. In this paper, therefore, we investigate peer effects in the workplace for a representative set of workers, firms, and occupations with a focus on peer effects in wages rather than productivity. Our estimation strategy which links the average permanent productivity of workers' peers to their wages circumvents the reflection problem and accounts for the endogenous sorting of workers into peer groups and firms. On average, we find only small peer effects in wages. We also find small peer effects in the type of high skilled occupations which more closely resemble those used in studies on knowledge spillover. In the type of low skilled occupations analyzed in existing studies on social pressure, in contrast, we find larger peer effects, about half the size of those identified in similar studies on productivity.
Keywords: J24; J31; 330; peer effects in the workplace